2006
DOI: 10.1080/j.1440-1614.2006.01922.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Management of Dual Relationships in Metropolitan, Regional and Rural Mental Health Practice

Abstract: No single strategy is used or appropriate for managing dual relationships in rural settings. Employers and professional bodies should provide clearer guidance for clinicians both in the management of dual relationships and the distinction between boundary crossings and boundary violation. Clinicians are clearly seeking to represent and protect the patients' interests; consideration should be given by consumer groups to steps that can be taken by patients to reciprocate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…This appeared to be a more significant issue in the community setting, despite the fact that the literature suggests there is often an enhanced risk for boundary violations in community settings (Andrews et al, 1995;Endacott et al, 2006;Green et al, 2003;Schank & Skovholt, 1997). Community practitioners were relatively under-represented in the training and dismissive of the relevance to their practice.…”
Section: Dismissivenessmentioning
confidence: 89%
See 1 more Smart Citation
“…This appeared to be a more significant issue in the community setting, despite the fact that the literature suggests there is often an enhanced risk for boundary violations in community settings (Andrews et al, 1995;Endacott et al, 2006;Green et al, 2003;Schank & Skovholt, 1997). Community practitioners were relatively under-represented in the training and dismissive of the relevance to their practice.…”
Section: Dismissivenessmentioning
confidence: 89%
“…This may not be the case, particularly within some work environments such as those where client-professional relationships are long term, emotionally intense and in rural and small community settings. These environments have been found to pose greater risks, particularly when practitioners are isolated and dilemmas are not discussed openly (Andrews, Griffiths, & Loney, 1995;Endacott et al, 2006;Green, Gregory, & Mason, 2003;Schank & Skovholt, 1997). Training that does exist in the workplace usually focuses on the risk management aspect, that is, the legal implications of professional boundary management rather than the transfer of knowledge and skills relating to critically reflective practice and ethical decision making (Boland-Prom & Anderson, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…While most studies of dual relationships in rural/remote settings agree that they are prevalent and accepted, not all agree that they are acceptable. Endacott et al (2006) conducted focus groups with mental health profesfocus groups with mental health professionals in urban, regional and rural Australia and reported that while dual relationships in rural areas were common, they were thought sometimes to have a negative impact for the client.…”
Section: ) Latin Americamentioning
confidence: 98%
“…10 The role of the rural clinician Rural clinicians are uniquely placed within their communities to see 'both sides of the coin' as a result of their position as an embedded residential member with personal investment in the social capital of the community. 36 Combined with their professional clinical roles, this creates a dual relationship, 37,38 and clinicians admit to the awkward balance that they have between their personal and professional lives. Clinicians struggle with the notion that supervision will enable them to operate effectively and ethically within small rural settings; however, professional and personal lives inevitably intertwine in the rural clinician's life experience.…”
Section: Harnessing Social Capital For Youth Mental Health: Case Exammentioning
confidence: 99%